What to ask : how to learn what customers need but don't tell you - Olson, Andrea Belk, 1976- (Ascent Audio, 2022)
Does capturing customer feedback feel like a pointless exercise? No matter the number of surveys, interviews, or studies conducted, we regularly fail to uncover those gems needed to make our organization stand out. It's no surprise given that "expert" guidance states the obvious, like "Ask open-ended questions," "Identify patterns," or "Extract insights." What's needed is a way to discover what we're missing. Traditional customer feedback methods ignore two essential sources of insight: context and behavior. These reveal the why behind the what, eliminating the ambiguity of open-ended customer feedback-and this requires a different approach. In What to Ask, author Andrea Belk Olson, CEO of applied behavioral science consulting firm Pragmadik, and head of the University of Iowa JPEC startup incubator, delivers a unique, cognitive method for discovering hidden customer needs, converting them quickly into differentiators, and avoiding the pitfalls of traditional research. Olson also details how individuals and organizations can better tune into customer needs by sharpening their strategic focus, cultivating customer-focused behaviors, and challenging cognitive biases